PENGEMBANGAN APLIKASI ENCODE DAN DECODE TREE MENGGUNAKAN BLOB CODE - Hijriani, Astria; Wamiliana, Wamiliana; Candra, Ady (Jurnal Komputasi, 2014)
Tree Structure is used widely to represent problems in daily life, especially in computer science and technology. One method that is used to represent a tree is Blob Code. In this research, we developed an application to Encode and Decode Tree using Blob Code. This application aims to simplify the process of changing tree into a blob code (encode) and the process of changing Blob code into the form of tree (decode).Â Keywords: Encode, Decode, Tree, representation Tree, Blob Code.